The Effect of Sustainable Marketing, Brand Image, Product Quality, and Customer Awareness on Purchase Intention - Bagus Yunianto Wibowo; Nanang Adie Setyawan; Destine Fajar Wiedayanti (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Increasing awareness of sustainability and the development of digital marketing have encouraged consumers to pay greater attention to environmental and product-related factors in purchasing decisions within the fashion industry. This study investigates the effect of sustainable marketing, brand image, product quality, and customer awareness on purchase intention toward fashion Micro, Small, and Medium Enterprises (MSMEs). The research is situated within the growing trend of sustainability-driven consumer behavior and increasing competition among local fashion MSMEs. The study contributes by empirically examining the integration of sustainability and marketing factors using a covariance-based approach. Data were collected from 150 consumers of fashion MSMEs through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS. The results reveal that sustainable marketing, brand image, and product quality have a significant positive effect on purchase intention, while customer awareness strengthens the influence of these variables on consumer decisions. The findings demonstrate that combining sustainability-oriented marketing strategies with strong brand image and high product quality can effectively increase purchase intention, particularly when supported by heightened customer awareness in the digital marketplace.